A Physician’s Nightmare: Fever of Unknown Origin - Sana Din; Farrukh Anwer; Mirza Beg (Case Reports in Pediatrics)
Fever of unknown origin (FUO) remains to be a challenge despite advancement in diagnostic technologies and procedures. FUO is considered when fever presents intermittently without an explanation. It has been linked to various etiologies, which makes it difficult to diagnose. We present the case of 18-month-old female with recurrent fever, splenomegaly, abdominal pain, and constipation. The workup for her symptoms revealed wandering spleen. Wandering spleen is a result from excessive laxity or absence of splenic ligaments. The patient underwent splenectomy and was advised to continue on Senna, Miralax, and high fiber diet. Her mother reported that the fever is no longer present and there is marked improvement in her constipation and abdominal pain after splenectomy.